Language learning strategies for reading comprehension: assessing the strategy use of young adults at beginners' level taking Chinese, German, Japanese or Spanish as foreign languages at university. Issue 2 (3rd March 2020) - Bruen, Jennifer
ABSTRACT: The purpose of this paper is to gain insights into the strategies employed by beginning learners of Spanish, German, Chinese and Japanese as Foreign Languages at university level in order to comprehend texts in their target languages. It also investigates possible relationships between strategic behaviour and success in reading comprehension tasks. Strategy use is assessed using qualitative analysis of reported strategic behaviour elicited from participants using open-ended questions, combined and compared with data generated using a modified sub-section of the Strategy Inventory for Language Learning [Oxford, R. 1990. Language Learning Strategies: What Every Teacher Should Know . Boston: Heinle and Heinle; Oxford, R. 2011. Teaching and Researching Language Learning Strategies . Harlow, UK: Pearson Education]. Implications of the study for the beginners' language classroom, and for language learning strategy research, particularly strategy measurement, are also considered.